Development of a Balinese Local Wisdom–Based Digital Flipbook to Enhance Elementary Students’ Science Learning Outcomes - Dewi, Ni Wayan Ari Kusuma; Dantes, Nyoman; Ardana, I Made (Jurnal Paedagogy, 2026)
This study aims to develop a Balinese local wisdom-based digital flipbook for ecosystem learning and to examine its validity, practicality, and effectiveness in improving fifth-grade elementary students’ science learning achievement. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The participants included expert validators, fifth-grade elementary school teachers, students involved in the practicality assessment, and 60 fifth-grade students who participated in the effectiveness testing. The research instruments comprised expert validation sheets, teacher and student practicality questionnaires, and a validated science learning achievement test administered before and after the intervention. Quantitative data were analyzed using descriptive statistics and inferential statistical analyses, including the Shapiro–Wilk normality test, homogeneity test, paired-samples *t*-test, and effect size analysis. The results indicated that the digital flipbook demonstrated excellent validity, with media and content validity scores of 96.00% and 95.99%, respectively. The media also showed excellent practicality, with teacher and student practicality scores of 98.91% and 98.98%, respectively. Furthermore, the effectiveness test revealed a statistically significant improvement in students’ science learning achievement following the implementation of the digital flipbook (p < 0.05), with a large effect size. These findings indicate that the Balinese local wisdom-based digital flipbook is valid, practical, and effective for supporting elementary science learning. By integrating the principles of Tri Hita Karana and the cultural traditions of Tumpek Wariga and Tumpek Uye into ecosystem learning, the digital flipbook also contributes to strengthening students’ digital science literacy while fostering the preservation of Balinese cultural values.